Efeitos do laser terapêutico de baixa intensidade e do treinamento resistido no metabolismo ósseo em ratos com diabetes mellitus tipo I - Silva, Tatiane Lopes Patrocinio da (Universidade Federal de São Carlos, 2013)
The DM is a chronic metabolic disorder characterized by a deficiency in the secretion or action of insulin, leading to a series of physiological changes that determine changes in normal operation of various organs and tissues, among which bone tissue is affected, leading to bone fragility. In this context, several treatments have been shown to accelerate bone metabolism. The Resistance Exercise (ER) is highly recommended for diabetics and among its beneficial effects promotes increased bone mineral density. The low-level laser therapy (LLLT) is able to stimulate the activity of osteoblasts, as well as increase the biomechanical properties of bone. However, its effects on bone metabolism in diabetic animals are not completely understood, and its action associated with the ER. Therefore, this study aimed to investigate the action of a protocol and resistance exercises LLLT applied individually or in combination on bone metabolism in diabetic rats. Fifty male Wistar rats were randomly divided into 5 experimental groups (N = 10): non-diabetic control group (CG), diabetic control (GD), diabetic group irradiated with laser (GL), trained diabetic group (TG) and trained group laser and diabetic (GTL). In the first study we evaluated the effects of LLLT on bone diabetic in three groups: GC, GD and GL. The GL was subjected to laser irradiation Ga-Al-As, 808 nm, 100 mW, 3.57 W/cm2, 0.028 cm2, 120J/cm2, 33s, for 18 sessions, on alternate days for 6 weeks. As the GL results showed increased cortical area and RUNX-2 immunoreactivity increased compared to GD. Furthermore, LLLT produced a significant increase in the strength of fracture, and bone mineral density (BMD and BMC), compared with DG. Therefore LLLT stimulated bone formation, reducing osteopenia animals. The second study evaluated the effects associated with ER LLLT in diabetic animals from group 4: GC, GD, GT and GTL. The ER consisted of climbing, load tied to the tail of the animal, and these loads were increased weekly throughout the training sessions, the GTL at the end of each session ER animals were irradiated with laser Ga-Al-As. Performed 6 weeks, 3 times per week, totaling 18 sessions. The GT and GTL showed increased cortical area, BMD and biomechanical properties. The BMC, fracture strength and stiffness were higher in GTL over the GT. Furthermore, immunohistochemical analysis showed that GT and GTL immunoassayed for RUNX-2 increased relative to GD. Already RANK-L immunoreactivity was moderated at GD and week on the others experimental groups. In conclusion, resistance exercise promoted osteoblast activation, with the increase in the biomechanical properties and BMD. The combination of exercise and LLLT, promoted the osteogenic potential additional effect of ER performed alone. Consequently, these data highlight the potential of exercise in the treatment of bone loss due to DM. Further studies should be conducted to provide additional information on the effects of LLLT as adjuvant therapy resistance exercise.
Keywords: Biotecnologia; Estreptozotocina; Exercício resistido; Fisioterapia; Diabetes mellitus; Tecido ósseo; Terapia laser de baixa intensidade; Diabetes mellitus; Bone tissue; Resistance exercise; Low intensity laser therapy; OUTROS